(untitled) (International Journal of Studies in Nursing, 2016)
Purpose: The study was conducted to investigate students’ perceptions on their clinical experience and the quality clinical placement. Methods: This was a cross-sectional descriptive study. One hundred and thirteen junior or senior nursing students participated in this study. Descriptive statistics were used to analyze the data. Results: Majority nursing students expressed un-satisfaction (57.52%) with the required hours of practicums. They experienced different quality of clinical placement between the cities. Direct nursing skills they practice were limited to doing chores (67.1%), charting (14.47%), providing education to patients and families (10.53%), giving medication (7.89%). 49.56% of the students did not satisfy with what they have received shift schedule which was given from hospitals. Conclusion: Simulation and scenario-centered education should be considered in Asian countries as one of replacement of clinical hours on-site. Future research warrants testing and clarifying the most appropriate clinical hours to the nursing undergraduates for their quality clinical placement.